Turnover intention and job satisfaction among quantity surveyors - Tan, Chin Keng; Mohamed Nor, Nik Nur Azirah; Yeoh, Kah Ching (IJTech Secretariat, 2018)
Within the framework of human resource management, this study focuses on the issues of turnover intention and job satisfaction in the context of quantity surveying firms. Turnover intention leads to actual turnover. Several factors have been identified to cause turnover intention. Quantity surveyors are among the key players in construction projects. A quantity surveyor is involved in financial and contractual matters from the initiation stage to the completion of construction. In relation to the technical employees of quantity surveying firms, the objectives of this research are 1) to determine whether these employees have turnover intention and 2) to determine their level of job satisfaction. The data for this study were collected through a questionnaire survey. The scope of the study is limited to technical staff in quantity surveying firms in Malaysia. A total of 600 questionnaires were distributed to quantity surveyors in these firms, and 183 responses were received within the given period of time. Thus, the response rate for this study is 30.5%. This study found that 38.8% of respondents intend to quit their current organizations. This percentage is considered high and impacts the staff stability of the firms. Turnover intention might be related to job dissatisfaction; the majority of respondents were not satisfied with most of the items in the constructs of opportunities and rewards, specifically, the salaries, bonuses, benefits, and promotion opportunities provided by the firms. In addition, the majority of the respondents expressed their dissatisfaction with the opportunities provided by their firms to participate in work-related decisions and suggestions.